Sustainable Development and Growth of the National Economy - Buranova Manzura Abdukadirovna; Khashimova Naima Abitovna (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article, the national economy, some definitions given to it, and the development of the economy of Uzbekistan along with the economy of the world countries in the current period of development, stable growth and the words of the President of the Republic of Uzbekistan and some literature are studied. All the given opinions and information are aimed at stabilization and liberalization of the economy.